Programs for children; The neglected world - Sarumpaet, Riris K. Toha (UI Scholars Hub, 2012)
What do children watch on Indonesian television? This article tries to answer this question in the conviction that TV shows made for children require an understanding of their needs in order to grow, motorically, cognitively, psychologically, socially, and culturally. From my own fieldwork and research done on the data provided by my informants, I found that on television during the time slot set for children there are shows that are not intended for children to watch. I also found that children enjoy two favourite television shows in Indonesia the most, which are not programs designated for children. The conclusion is that Indonesian television pays little attention to children's needs, and children are neglected.